The Effect Of Mentoring, Creativity And Risk On The Entrepreneurial Decisions Of Generation Z In Bengkulu City - Hidayat, Rahmat; Soleh , Ahmad; Yanti , Rina Trisna (Journal of Business Management, 2025)
This study aims to analyze the influence of mentoring, creativity, and risk on the entrepreneurial decisions of Generation Z in Bengkulu City. Using a quantitative approach with multiple linear regression methods, this study involved 130 Generation Z respondents domiciled in Bengkulu City. Data were collected through questionnaires and analyzed using SPSS to test the partial and simultaneous effects between independent variables (mentoring, creativity, risk) on the dependent variable (entrepreneurial decisions). The regression equation obtained is Y = 6.214 + 0.312X₁ + 0.451X₂ + 0.278X₃, indicating that all independent variables have a positive influence on entrepreneurial decisions. The test results show a coefficient of determination (R²) of 0.713, meaning that 71.3% of the variation in entrepreneurial decisions can be explained by mentoring, creativity, and risk together, while the remaining 28.7% is influenced by other factors outside the model. The t-test indicates that the variables creativity (t = 4.236; sig = 0.000) and risk (t = 3.851; sig = 0.001) have a significant partial effect, while mentoring (t = 1.842; sig = 0.068) does not have a significant effect individually. The F-test yielded F count = 34.512 with a sig = 0.000, indicating that all three variables significantly influence entrepreneurial decisions simultaneously. Thus, increased creativity, risk management skills, and targeted mentoring can encourage Generation Z in Bengkulu to dare to become entrepreneurs.